O papel dos esquemas emocionais na transgeracionalidade do processo de socialização das emoções negativas - Palmeira, Lara (2011)
Recently, with the resurgence of interest in the field of emotions within various domains of psychology, increased attention has been given to the study of the emotion socialization process. The present study focuses on this process, searching evidences for a transgenerational effect, in a sample of 172 mothers of 8 to 12 yearsold children. The results confirmed the existence of the transgenerational effect and showed that the relation between family expressivity and mothers reactions to children’s negative emotions was mediated by emotional schemas.